2020
DOI: 10.51894/001c.17543
|View full text |Cite
|
Sign up to set email alerts
|

Lingual Osseous Choristoma: A Systematic Review of Lesion Presentation, Histology, and Morphology

Abstract: INTRODUCTION Osseous choristomas of the tongue are rare, benign tumor-like lesions composed of abnormally placed bone and cartilage tissue. The few publications to date concerning this condition have been primarily limited to case reports. This systematic review aimed to clarify the clinical presentations of osseous choristomas and how to delineate them from other oral pathologies. METHODS The authors utilized PubMed, Embase, and Cochrane Library reference databases from 1971 to mid-2020. Search terms were “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
15

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(33 citation statements)
references
References 15 publications
0
14
0
15
Order By: Relevance
“…No evidence of spontaneous loss or malignant transformation has been reported. No case of pediatric lingual osseous choristoma showed any sign of recurrence [ 7 ], while only two recurrent nonpediatric cases of the buccal mucosa lesion were reported [ 56 , 57 ]. Long et al reported that the recurrent lesion could have arisen as a result of the surgical trauma caused by the removal of the original lesion; however, this theory could not explain the occurrence of the original lesion because the patient denied any history of trauma [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No evidence of spontaneous loss or malignant transformation has been reported. No case of pediatric lingual osseous choristoma showed any sign of recurrence [ 7 ], while only two recurrent nonpediatric cases of the buccal mucosa lesion were reported [ 56 , 57 ]. Long et al reported that the recurrent lesion could have arisen as a result of the surgical trauma caused by the removal of the original lesion; however, this theory could not explain the occurrence of the original lesion because the patient denied any history of trauma [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lingual masses can include osseous choristoma or other lesions such as fibroma, papilloma, pyogenic granulomas, squamous cell carcinomas, or hemangiomas [ 6 ]. Even though some patients may be asymptomatic, a wide array of symptoms, including gagging, dysphagia, foreign body sensation, throat irritation, discomfort, and pain, have been reported [ 7 ]. Physical examination and diagnostic imaging may assist in identifying the mass; however, a definitive diagnosis requires histologic examination.…”
Section: Introductionmentioning
confidence: 99%
“…El coristoma es definido como el crecimiento de tejido normal en locaciones anormales, rara vez observado en cavidad oral y, cuando se presentan, son con mayor frecuencia compuestos de tejido óseo o cartilaginoso. Otras composiciones menos frecuentes incluyen tejido glial periférico, glándulas sebáceas o tejido gastrointestinal 1 . El coristoma óseo lingual se refiere al crecimiento heterotópico de tejido óseo maduro dentro de tejido blando lingual.…”
unclassified
“…El coristoma óseo lingual se refiere al crecimiento heterotópico de tejido óseo maduro dentro de tejido blando lingual. Es una lesión rara y benigna de la cavidad oral que afecta más comúnmente el dorso de la lengua con menos de 100 casos reportados en la literatura desde su definición en el año 1913 1,2 . En ocasiones genera sintomatología de estimulación mecánica, como disfagia y náuseas.…”
unclassified
See 1 more Smart Citation